The mean to your problem is 87.5
Answer:
(-2 , -3) and (0.6 , 4.8)
Step-by-step explanation:
y=3x +3
(x - 2)² + y² = 25
(x - 2)² + (3x +3)² = 25
x²-4x+4+9x²+18x+9-25=0
10x²+14x-12=0
5x²+7x-6=0
(x+2)(5x-3)=0
x = -2 or x = 3/5 (-0.6)
y = -3 or y = 4 4/5 (4.8)
Answer:
false
Step-by-step explanation:
The answer is 20 because five times four is 20 so all you do is multiple
Answer:
○ I, II, and III
Step-by-step explanation:
Long explanation short, dividing an expression by 2 is the exact same as multiplying an expression by ½. That is to say, dividing a term is the exact same as multiplying by its multiplicative inverse, so all three of these would qualify.
I am joyous to assist you anytime.